(untitled) (Journal of actual problems of jurisprudence, 2019)
Тhe article describes the antisocial activities of teenagers-criminal offences are dealt with on a scientific level, the causes of their Commission. It is not a secret that teenagers first of all stand as the main «serious» problem of a criminal offense, but fight against it is conducted daily, every year increases, doesn’t decrease. Of course, this does not mean that the criminal offense «grows» every hour, every day, every month, and the fight against crime is not conducted. In the framework of state programs at the regional level, the district and the city is working, which has no analogues of criminal offenses and criminal offenses, gives results. Here we say that a child who has committed one criminal activity, «contribution» to the statistics in the second, third and even more times. These statistics are supplemented by children who attend criminal activities under the influence of adults and children who are given free time. In any case, the fate of such children will not leave indifferent any member of society. The author aims at the scientific disclosure of deviant behavior, analyzing the works of domestic and Russian scientists, taking into account the opinion of scientists. In the article the author reveals in detail the causes of deviant behavior of adolescents committing criminal offenses, the reasons for its prevention, prevention and effectiveness of the fight against criminal offenses. Key words: deviant behavior, criminal offense, prevention, prevention, criminal law effectiveness, efficiency.